2020
DOI: 10.1051/e3sconf/202017502010
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral aquaculture in the reservoirs of the Kuban basin

Abstract: The article provides calculations and recommendations for fisheries development and improvement of fish productivity of reservoirs in the Kuban basin. The taxonomic composition of water biological resources has been studied and the natural bio-production potential of some reservoirs in the South of Russia has been determined. It is proposed for the purpose of pastoral aquaculture to produce directed formation of the ichthyofauna of reservoirs by yearlings Hypophthalmichthys molitrix, Hypophthalmichthys nobilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Studies have shown that the phytoplankton of riverbed ponds located on the rivers of the Azov-Kuban plain is represented by 125 taxa of algae belonging to 9 groups: Chlorophyta -37 taxa, of which Protococcophyceae -28, Volvocophyceae -6, Desmidiales -3, Bacillariophyta -33 taxa, Euglenophyta -16, Cyanophyta -26, Pyrrophyta -8, chrysophyta -3 and Xanthophyta -2 taxa. The results obtained are comparable to previous studies within the Azov-Kuban plain [8] Zooplankton is represented by three typically planktonic groups of organisms: Rotatoria, Copepoda, and Cladocera [9,10]. The zooplankton species analysis identified invertebrates belonging to 24 taxa: Rotatoria-16, Copepoda-4, Cladocera -4.…”
Section: Hydrobiological Characteristics Of Reservoirs Of the Kirpili Riversupporting
confidence: 86%
“…Studies have shown that the phytoplankton of riverbed ponds located on the rivers of the Azov-Kuban plain is represented by 125 taxa of algae belonging to 9 groups: Chlorophyta -37 taxa, of which Protococcophyceae -28, Volvocophyceae -6, Desmidiales -3, Bacillariophyta -33 taxa, Euglenophyta -16, Cyanophyta -26, Pyrrophyta -8, chrysophyta -3 and Xanthophyta -2 taxa. The results obtained are comparable to previous studies within the Azov-Kuban plain [8] Zooplankton is represented by three typically planktonic groups of organisms: Rotatoria, Copepoda, and Cladocera [9,10]. The zooplankton species analysis identified invertebrates belonging to 24 taxa: Rotatoria-16, Copepoda-4, Cladocera -4.…”
Section: Hydrobiological Characteristics Of Reservoirs Of the Kirpili Riversupporting
confidence: 86%
“…The rivers of the Azov-Kuban plain Yeya, Chelbas, Beysug, Kirpili, Ponura, Albashi, Yaseni and their tributaries are regulated and represent a cascade of reservoirs (ponds-reservoirs) with an area of 5-10 to 300-500 hectares or more. According to Kubangiprovodkhoz, there are about 1300 reservoirs on the rivers of the Azov-Kuban plain, with a total area of about 50 thousand hectares [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The fertility of large females can exceed 100 thousand eggs, fluctuations of 4-140 thousand. The diameter of the oocytes is 2-3 mm, the weight is 8-9 mg. Development varies from 4 to 9 days depending on the water temperature [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is able to reproduce regularly with an interval of 25-80 days. [9]. Channel ponds located on the rivers of the Azov-Kuban plain (Yeya, Kirpili, Chelbas, Beysug, Kalaly and their tributaries) can be used to expand the cultivation of sturgeon species of fish (sterlet) in the Krasnodar Territory.…”
Section: Introductionmentioning
confidence: 99%